Eksplorasi Media Seni Rupa Dua Dimensi Menggunakan Mika Akrilik - Ramatullah, Stera Laksana (Institut Seni Indoensia Surakarta, 2021)
ABSTRACTThe exploration of the art medium is intended as a step to gain new knowledge and experience using the main material, namely acrylic mica in creating works of fineart to find novelty or new opportunities in the art medium. Acrylic mica is selected because it has the characteristics of being transparent, strong, flexible, durable (not easily broken), non-absorbent, and lighter in weight compared to glass. This advantage is an interesting opportunity if it can be utilized properly so that it becomes one of the alternative mediums of painting besides conventional media such as canvas, paper, recin, and wood.Keywords: exploration, media, acrylic mica, fine art